Bibliometric computational analysis of the scientific literature on burnout and its effect on health and safety of employees - Andy Wai Kan Yeung; Olena Litvinova; Maima Matin; Michel-Edwar Mickael; Maria Kletecka-Pulker; Atanas G. Atanasov; Harald Willschke; Thomas Wochele-Thoma (Exploration of Digital Health Technologies)
Background: The main theme of research literature on burnout has yet to be investigated. Aims: This bibliometric study evaluated the research literature on burnout and health, indexed in Web of Science (WoS), to reveal its expansion and the most prolific authors, institutions, countries, journals, and journal categories. The recurring themes of the literature were also identified. Methods: In December 2023, the WoS Core Collection database was queried with: TS = [(“burnout*” OR “burn out*” OR “burn-out*”) AND (“health*” OR “illness*” OR “disease*” OR “well-being*” OR “wellbeing*”)]. The search yielded publications with these words presented in their title, abstract, or keywords. No filter was placed to restrict the search. Publication and citation counts were recorded directly from the database, whereas subsequent analyses were performed with VOSviewer. Results: The search yielded 26,492 publications. The literature has been growing steadily in the 2000s and more quickly in the 2010s. Nearly one-third of the publications had contributions from the United States. The most prolific journals involved some open-access mega-journals and journals from psychology, medicine, and nursing. Depression and anxiety associated with burnout were recurring themes in the literature. The research community has been explaining burnout by the highly cited Job Demands-Resources (JD-R) model. Discussion: This work demonstrated the usefulness of a bibliometric analysis to identify key stakeholders and major themes of burnout research.